Endure: Augmented reality fitness mobile application - Nair Y.N.I.; Azman F.; Rahim F.A.; Cheng L.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Augmented reality; First person; Fitness; Game; Immersive technologies; Malaysians; Mobile; Mobile applications; Virtual selves; Health